Antioxidant and Antimicrobial Efficacy of Various Solvent Extracts of Seed of Rudrakshya (Elaeocarpus ganitrus) from Ilam District of Nepal - Bhatt, Bishan Datt; Dahal, Purushottam (Journal of Nepal Chemical Society, 2019)
Elaeocarpus ganitrus (Rudrakshya) is an evergreen tree found in tropical and sub-tropical regions and has been commonly used in traditional medicine against various diseases. In the present study, phytochemical constituents, antimicrobial activity and antioxidant property of seed of Elaeocarpus ganitrus have been evaluated in hexane, ethyl acetate, acetone and methanol extracts. The phytochemical screening showed the presence of alkaloids, flavonoids, phenols, tannins, steroids, carbohydrates, saponins, terpenoids etc. The antibacterial test showed a significant zone of inhibition against Escherichia coli, Salmonella typhi and Staphylococcus aureus with the maximum zone of inhibition of 20 mm. The study showed that these extracts can be used as antimicrobial substances against various bacteria. Antioxidant activity of the methanol, acetone and ethyl acetate extract were studied by DPPH radical scavenging assay. The extracts showed significant antioxidant activity. Among the IC50 values of different extracts on DPPH assay for antioxidant determination, methanol seed extract showed the lowest value of 28.09 µg/mL. This means methanol extract of seed showed the significantly high antioxidant properties. Calculation of total phenolic content showed a significant amount of phenolic content in different solvent extracts. Methanol seed extract showed the highest total phenolic content of 174.6 mgGAE/g. Similarly, methanol seed extract showed the highest total flavonoid content of 107.13 mgQE/g. These results suggest that the seeds of the Elaeocarpus ganitrus (Rudrakshya) plant from the Ilam district of Nepal possess high antimicrobial and antioxidant properties and thus, the plant can be used in the discovery of new bioactive natural products.